Strategies of Regional Organizations in Addressing the Repercussions of Forced Displacement Caused by Armed Conflicts: An Analytical Study (Comprehensive Journal of Science, 2026)
This research aims to analyze and evaluate the role played by regional organizations as pivotal actors possessing the advantage of geographical proximity to crises. The research problem lies in the strategic gap between legal frameworks and complex field realities, particularly in light of the clash between the requirements of national sovereignty and humanitarian obligations.The study employs a descriptive-analytical approach to diagnose the phenomenon of displacement, and a legal approach to ground the foundations of regional intervention in light of Chapter VIII of the UN Charter and International Humanitarian Law. Additionally, it utilizes a case study approach (focusing on the African Union) and a prospective approach.The research concludes that while regional organizations have succeeded in building a sophisticated legal arsenal, such as the Kampala Convention, their operational effectiveness remains hindered by structural obstacles. Most notably, these include financial dependency on international donors and a lack of technical independence in early warning systems. The study suggests that sustainable solutions require moving beyond emergency relief toward the socio-economic reintegration of displaced persons to ensure social peace. Furthermore, reinforcing sovereignty as a responsibility serves as the legal pathway to activating the role of regional organizations in protecting the rights of the displaced and ensuring regional security.